POLIGAMI DALAM PERSPEKTIF SOSIOLOGI (APLIKASI PENDEKATAN TEORI STRUKTURAL FUNGSIONAL) - FATA, NAHRIYAH (IAIN Padangsidimpuan, 2014)
Poligamy is a marriage promblem most debatedly and controversially. For some people, poligamy is denied by various arguments normatively, psicologically and so far it is always related to irrational right in gender. Looking the phenomena, the writer tries exploring poligamy in prespective of sociology by functional structural approach using A-G-I-L concept, where it gives finally that poligamy is then more functional, there are some requirements: Adaptation, to the environment, goal attainment, integration, latent pattern maintenance.